Design of a Radiation Hardened DC-DC Boost Converter - Liu Zhi; Yu Hong-bo; Liu You-bao; Ning Hong-ying (2010 2nd International Conference on Information Engineering and Computer Science, 2010)
A radiation hardened monolithic DC-DC boost converter is presented in this paper. The RHBD (Radiation-Hardening by Design) techniques applied to Radiation Hardened DC-DC Boost Converter, which has been fabricated with a standard commercial 0.35-μm CMOS process. Both circuit and device-level RHBD techniques are employed to improve the radiation tolerant abilities. All power switches, feedback control circuit, and current-sensing circuit are fabricated on-chip. Only one off-chip inductor and one off-chip capacitor are needed at the power stage, and no off-chip inductor current sensor is needed. In layout design, MOS transistors using H-GATE is to reduce the impact of TID (Total Ionizing Dose). By momentarily connecting a capacitor between the noninverting input of the error amplifier and the output of the amplifier forced the circuit to restart and allowed the circuit to continue operating to a high total dose level. The radiation experiment results show that the circuit survived 120 krad (Si) total ionizing dose (TID) with no degradation in function.